Keefektifan Pemimpin Transformasional Pesantren Bagi Peningkatan Mutu Lembaga Pendidikan Islam - Moh. Hasan Afini Maulana (Indonesian Journal of Islamic Educational Management, 2021)
The article entitled The Effectiveness of Transformational Leaders of Islamic Boarding Schools For Quality Improvement of Curriculum The Islamic Education Institution focuses on wetting as follows: 1) How do leaders understand? 2) What is the authority of the pesantren leader? 3) how is leadership theory? 4) What about transformational leadership in boarding schools? So it requires data to answer the discussion above by describing and analyzing from various directions on public relations management in educational institutions. So the purpose of this discussion will give birth to concrete answers regarding: 1) Understanding of leaders 2) Authority of pesantren leaders 3) Leadership theory 4) Transformational leadership of boarding schools. Some of these discussions are focused or focused on the scope of education or educational institutions, especially Islamic boarding schools. More than that, Leadership plays a privotal role in an organization or institution. Leadership does not only play a role in directing and organizing the organization members’ potentials in order to achieve its objectives or goals set out by the organization. In addition, the leadership also plays a key role in arranging the rythm of the organization’s movement. The significance of leadership can aslo be found in the world of pesantren. As an organization, educational succes rate in pesantren is also affected by types, kinds and styles of leadership. This paper offers concept of transformational leadership as a means of advancing pesantrens.